Calculus 8th Edition

Published by Cengage
ISBN 10: 1285740629
ISBN 13: 978-1-28574-062-1

Chapter 2 - Derivatives - 2.3 Differentiation Formulas - 2.3 Exercises - Page 140: 10


$B'(y) = -6cy^{-7}$

Work Step by Step

$B(y)=cy^{-6}$ lets use the Formula $(cf)'=cf'$ then $B'(y) = (cy^{-6})' = c(y^{-6})'$ and the Formula $(x^{n})'=nx^{n-1}$ then $B'(y) = (cy^{-6})' = c(y^{-6})'=c (-6y^{-7})=-6cy^{-7}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.